Unconventional times in higher education: Lived experiences of South African student support champions during the Covid-19 pandemic - Scholtz, D.; Williams, S. (South African Journal of Higher Education, 2025)
The COVID‒19 pandemic necessitated swift changes to remote teaching and learning. This study explored the experiences of student support champions comprising teaching assistants, tutors, mentors, and retention officers) in providing affective and content support via remote modalities to first‒year students. The study focused on insights gained during remote learning. This adaptation to change speaks to resilience thinking, ‘being able to withstand or overcome adversity and unpleasant events and successfully adapt to change and uncertainty’. Learning to be resilient and adaptable to rise above challenges, is simultaneously transformative to create new ways of thinking to deal with current situations. This study resides within the interpretivist paradigm and draws on the subjective experiences and understandings of research participants within a university of technology. Surveys were conducted to garner insights and experiences and were analysed according to emergent themes of challenges, improvements, and future practices. Data revealed that despite the demands placed on student support champions, they managed to cope with their studies and acquired attributes, dispositions, and values beyond the formal curriculum. Thus the study shows that times of complexity present opportunities for resilience and transformation to changing circumstances.